Vortext: Derrida, Lacan, Life (Imaginations: Journal of Cross-Cultural Image Studies, 2025)
This research creation project is a poetic rendering of a portion of the story of getting my PhD. The relationship between the text and vortex of theory (Derridean, Lacanian among others) and the quotidian, generate this “vortext” of prose poems. Inspring the research are neighbours, dinner menus, Sir Gawain and the Green Knight, the news, Betty (Davis, Crocker, Goodwin, Boop), Homer, Dante, the Inquisition, my dissertation defence; Derrida’s essay on différance, his ideas on the universal and autobiography, and his texts Archive Fever and Acts of Religion; and Lacan’s reflections on lack, the absence of the universal woman (Seminar XX), and the objet a and Das Ding (Seminar XI). Thus the poetry of scholarship.